Effect of Dietary Berry Supplementation on Antioxidant Biomarkers in Adults with Cardiometabolic Risks: A Systematic Review of Clinical Trials - Macy M. Helm; Tolu Alaba; Dorothy Klimis-Zacas; Kenneth Izuora; Arpita Basu (MDPI AG, 2023)
Cardiometabolic conditions are closely associated with inflammation and oxidative stress. Dietary berries may serve as a beneficial nutrition intervention to address the features of cardiometabolic dysfunction and associated oxidative stress. The high antioxidant status of dietary berries may increase antioxidant capacity and reduce biomarkers of oxidative stress. This systematic review was conducted to investigate these effects of dietary berries. The search was conducted using PubMed, Cochrane Library, Web of Science, and citation searching. Through this search we identified 6309 articles and 54 were included in the review. Each study's risk of bias was assessed using the 2019 Cochrane Methods' Risk of Bias 2 tool. Antioxidant and oxidative stress outcomes were evaluated, and the magnitude of effect was calculated using Cohen's d. A range of effectiveness was reported in the included studies and the quality of the studies differed between the parallel and crossover trials. Considering the inconsistency in reported effectiveness, future investigations are warranted to determine the acute and sustained reductions of oxidative stress biomarkers from dietary berry intake (PROSPERO registration# CRD42022374654).